Molecular genetic analysis of Suppressor 2 of zeste identifies key functional domains. - Emmons, R.B.; Genetti, H.; Filandrinos, S.; Lokere, J.; Wu, C.T. (Genetics, 2009)
The Su(z)2 complex contains Posterior sex combs (Psc) and Suppressor 2 of zeste [Su(z)2], two paralogous genes that likely arose by gene duplication. Psc encodes a Polycomb group protein that functions as a central component of the PRC1 complex, which maintains transcriptional repression of a wide array of genes. Although much is known about Psc, very little is known about Su(z)2, the analysis of which has been hampered by a dearth of alleles. We have generated new alleles of Su(z)2 and analyzed them at the genetic and molecular levels. Some of these alleles display negative complementation in that they cause lethality when heterozygous with the gain-of-function Su(z)2(1) allele but are hemizygous and, in some cases, homozygous viable. Interestingly, alleles of this class identify protein domains within Su(z)2 that are highly conserved in Psc and the mammalian Bmi-1 and Mel-18 proteins. We also find several domains of intrinsic disorder in the C-terminal regions of both Psc and Su(z)2 and suggest that these domains may contribute to the essential functions of both proteins.